Efficient magnetism breaking method for low-magnetic-conductivity nanocrystalline magnetism isolating sheet
By using bump roll crushing technology and thinner and flexible silicone protective film in the production of nanocrystalline magnetic wafers, the problem of difficult to reduce nanocrystalline magnetic permeability in the prior art is solved, and high-efficiency and low-loss crushing is achieved. The effect improves production efficiency and quality.
Patent Information
- Application Number
- CN202411787044.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nanocrystal magnetic spacer production process is difficult to effectively reduce the magnetic permeability of nanocrystals, resulting in large eddy current loss in wireless charging. The traditional magnetic crushing method is low in efficiency and high in cost, and does not have the feasibility of mass production.
The bump roll crushing technology is used to combine thinner and better flexible silicone protective film to achieve simultaneous crushing of multi-layer nanocrystals, significantly improving the efficiency and quality of the crushing.
It achieves rapid breaking to a lower magnetic permeability, reduces the loss of nanocrystalline magnetic separator, improves the efficiency and quality of the magnetic crushing, facilitates the improvement of production efficiency and reduces costs.
Smart Images

Figure CN119456101A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials and wireless charging, and in particular relates to a high-efficiency magnetic fragmentation method for a low-magnetic-permeability nanocrystalline magnetic isolation sheet. Background Art
[0002] With the development of inductive wireless charging technology, wireless charging is increasingly used in consumer electronics (such as smart phones and watches), daily home (such as wireless smart kitchens), electric vehicles, industrial production (robots, smart unmanned logistics vehicles), etc. Magnetic isolation sheets are crucial and indispensable in inductive wireless charging. They can effectively increase the inductance of wireless charging modules, while restraining electromagnetic fields, preventing electromagnetic field leakage from interfering with electronic components, and reducing eddy current heat generation of electromagnetic fields on surrounding metals. Iron-based nanocrystals (main elements Fe, Cu, Nb, Si, B) are widely used in wireless charging because of their high saturation magnetic induction intensity and magnetic permeability, low coercivity and loss. However, nanocrystals will generate eddy currents during wireless charging due to their low resistivity, causing a lot of energy loss. Therefore, nanocrystalline magnetic isolation sheets usually need to be fragmented by crushing the nanocrystals to reduce their eddy current losses. Generally speaking, the more cracks in the nanocrystals and the smaller and more uniform the fragments, the lower their magnetic permeability and the smaller their eddy current losses. With the popularity of wireless charging, the demand for wireless charging magnetic isolation sheets is increasing, and the requirements for low loss of magnetic isolation sheets are also increasing. The existing production process of nanocrystalline magnetic isolation sheets generally uses a magnetic crushing roller with grid-shaped or striped patterns, which makes it difficult to crush nanocrystals to a magnetic permeability of 500 or lower. If you need to crush to a lower magnetic permeability, you usually need to crush it in a single layer, increase the crushing pressure, or increase the number of crushing times, but this will not only reduce the crushing efficiency, but also increase the equipment loss, and it is not feasible for mass production. In addition, the way to crush nanocrystals is generally to first coat the surface of the nanocrystalline strip with a protective film to make the crushing more uniform and reduce damage to the nanocrystals. The existing process protective film generally uses a 50μm or 75μm PET protective film, which is thick and has poor elasticity. The protective film bears and offsets most of the crushing pressure, resulting in low crushing efficiency. Therefore, how to economically and feasibly produce low-permeability nanocrystalline magnetic isolation sheets has become a research hotspot in the industry. Summary of the invention
[0003] In view of the shortcomings and deficiencies of the above prior art, the purpose of the present invention is to provide an efficient method for crushing low-permeability nanocrystalline magnetic isolation sheets. The crushing method of the present invention adopts convex roller crushing, which has more concentrated local force, strong penetration, high crushing efficiency, and can achieve simultaneous crushing of multiple layers of nanocrystals; and by matching with a thinner and more flexible protective film, it can significantly improve the crushing efficiency and crushing quality.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0006] (1) The composite multilayer nanocrystalline strip is attached by double-sided adhesive and then covered with a protective film;
[0007] (2) crushing the multilayer nanocrystalline strip with the protective film on the surface in step (1) by using a convex roller to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet;
[0008] The protective film in step (1) is an organic silicon protective film prepared by the following method:
[0009] 1) mixing hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent, then adding a chloroplatinic acid isopropanol solution catalyst and heating for reaction to obtain an epoxy polysiloxane solution;
[0010] 2) The epoxy polysiloxane solution obtained in step 1) is mixed evenly with the polyetheramine, and dried and cured to form a film to obtain an organosilicon protective film.
[0011] Furthermore, the thickness of the double-sided tape in step (1) is 1 to 5 μm; and the thickness of the nanocrystalline ribbon is 14 to 25 μm.
[0012] Furthermore, the number of layers of the nanocrystalline ribbon in step (1) is 2 to 4 layers.
[0013] Furthermore, the thickness of the protective film in step (1) is 5 to 50 μm.
[0014] Furthermore, the hydrogen-containing silicone oil in step 1) is a hydrogen-containing silicone oil having a number average molecular weight of 1000 to 10000 and a hydrogen content of 0.2 to 1 wt.%.
[0015] Furthermore, the amount of allyl glycidyl ether used in step 1) is 5% to 30% of the mass of the hydrogen-containing silicone oil.
[0016] Furthermore, the organic solvent in step 1) is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol.
[0017] Further preferably, the amount of the organic solvent used is 100% to 200% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether.
[0018] Furthermore, the temperature of the heating reaction in step 1) is 80-90° C. and the time is 2-8 hours.
[0019] Furthermore, the polyetheramine in step 2) is an amino-terminated polyoxypropylene ether and an amino-terminated polyoxyethylene ether with a molecular weight of 400 to 5000. Preferably, the amino-terminated polyoxyethylene ether has a molecular weight of 1000 to 3000. The present invention uses polyetheramine to cure epoxy polysiloxane, and the resulting protective film can achieve good strength and elasticity at the same time.
[0020] Further preferably, the amount of the polyetheramine used is 50% to 150% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether.
[0021] Furthermore, the drying and curing film-forming in step 2) refers to coating drying and curing film-forming or casting drying and curing film-forming at a temperature of 60 to 100°C.
[0022] Furthermore, the convex point roller in step (2) is a roller having pyramid-shaped convex points (such as the attached Figure 1 The crushing pressure is 10 to 200 MPa.
[0023] Furthermore, the crushing in step (2) refers to crushing to a magnetic permeability of less than 500.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention, through a specific crushing roller shape and a thinner and more flexible protective film, can achieve simultaneous crushing of multiple layers of nanocrystals at one time, and quickly crush them to a lower magnetic permeability (for example, 2 to 4 times can crush them to a magnetic permeability of about 100, while conventional crushing requires 10 to 30 times). This can effectively reduce the loss of nanocrystalline magnetic isolation sheets, and greatly improve the efficiency and quality of magnetic crushing, which is convenient for improving the production efficiency of low magnetic permeability nanocrystalline magnetic isolation sheets and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the structure of the pyramid-shaped structure bump.
[0027] Figure 2 Schematic diagram of the structure of the nanocrystal stack obtained in Example 1.
[0028] Figure 3 This is a schematic diagram of crushing using a convex point roller in Example 1. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0030] Example 1
[0031] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0032] (1) By mass, 100 parts of hydrogen-containing silicone oil with a number average molecular weight of 5600 and a hydrogen content of 0.52wt.%, 20 parts of allyl glycidyl ether and 150 parts of toluene were mixed, and a 100ppm platinum content of chloroplatinic acid isopropanol solution was added under nitrogen protection, heated to 85°C and stirred for 4h to obtain an epoxy polysiloxane solution. Then, the epoxy polysiloxane solution was mixed with 100 parts of amino-terminated polyoxyethylene ether with a molecular weight of 2000, and cast, dried and cured at 80°C to form a film to obtain a silicone protective film (PDMS-1) with a thickness of 25μm.
[0033] (2) Three layers of 18 μm thick iron-based nanocrystalline ribbons are bonded together by using a 5 μm thick double-sided adhesive tape, and then the protective film obtained in step (1) is coated on the surface to obtain a nanocrystalline laminate. The schematic diagram of the structure of the obtained nanocrystalline laminate is shown in FIG2.
[0034] (3) The nanocrystalline stack of step (2) is crushed by a convex roller with pyramid-shaped convex points (the crushing diagram is shown in FIG. Figure 3 The crushing pressure was 100 MPa, and the crushing was repeated 3 times to obtain a low permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 127. There was no obvious rupture of the organic silicon protective film after crushing.
[0035] Example 2
[0036] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0037] (1) Two layers of iron-based nanocrystalline strips are bonded together by using double-sided adhesive tape, and then the protective film obtained in Example 1 is coated on the surface to obtain a nanocrystalline laminate.
[0038] (2) The nanocrystalline laminate of step (1) is crushed by a convex roller with pyramid-shaped convex points, the crushing pressure is 200 MPa, and the crushing is repeated twice to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 115. After the crushing, the organic silicon protective film has no obvious cracks.
[0039] Example 3
[0040] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0041] (1) The epoxy polysiloxane solution prepared in Example 1 was mixed evenly with 100 parts of terminal amino polyoxyethylene ether with a molecular weight of 1000, and the mixture was cast, dried and cured at 80° C. to obtain a silicone protective film (PDMS-2) with a thickness of 40 μm.
[0042] (2) Three layers of 18 μm thick iron-based nanocrystalline strips are bonded together by using a 5 μm thick double-sided tape, and then the protective film obtained in step (1) is coated on the surface to obtain a nanocrystalline laminate.
[0043] (3) The nanocrystalline laminate of step (2) was crushed by a convex roller with pyramid-shaped convex points, the crushing pressure was 120 MPa, and the crushing was repeated 4 times to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 140. After the crushing, the organic silicon protective film had no obvious cracks.
[0044] Example 4
[0045] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0046] (1) The epoxy polysiloxane solution prepared in Example 1 was mixed evenly with 100 parts of terminal amino polyoxyethylene ether with a molecular weight of 400, and the mixture was cast, dried and cured at 80° C. to obtain a silicone protective film (PDMS-3) with a thickness of 25 μm.
[0047] (2) Three layers of 18 μm thick iron-based nanocrystalline strips are bonded together by using a 5 μm thick double-sided tape, and then the protective film obtained in step (1) is coated on the surface to obtain a nanocrystalline laminate.
[0048] (3) The nanocrystalline laminate of step (2) was crushed by a convex roller with pyramid-shaped convex points, the crushing pressure was 160 MPa, and the crushing was repeated 3 times to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 132. After the crushing, the organic silicon protective film had no obvious cracks.
[0049] Example 5
[0050] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0051] (1) The epoxy polysiloxane solution prepared in Example 1 was mixed evenly with 100 parts of terminal amino polyoxyethylene ether with a molecular weight of 3000, and the mixture was cast, dried and cured at 80° C. to form a film, thereby obtaining a 25 μm thick organic silicone protective film (PDMS-4).
[0052] (2) Three layers of 18 μm thick iron-based nanocrystalline strips are bonded together by using a 5 μm thick double-sided tape, and then the protective film obtained in step (1) is coated on the surface to obtain a nanocrystalline laminate.
[0053] (3) The nanocrystalline laminate of step (2) was crushed by a convex roller with pyramid-shaped convex points, the crushing pressure was 150 MPa, and the crushing was repeated 3 times to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 116. After the crushing, the organic silicon protective film had no obvious cracks.
[0054] Example 6
[0055] A high-efficiency magnetic fragmentation method for a low-permeability nanocrystalline magnetic isolation sheet comprises the following steps:
[0056] (1) The epoxy polysiloxane solution prepared in Example 1 was mixed evenly with 100 parts of terminal amino polyoxyethylene ether with a molecular weight of 5000, and the mixture was cast, dried and cured at 80° C. to obtain a silicone protective film (PDMS-5) with a thickness of 25 μm.
[0057] (2) Three layers of 18 μm thick iron-based nanocrystalline strips are bonded together by using a 5 μm thick double-sided tape, and then the protective film obtained in step (1) is coated on the surface to obtain a nanocrystalline laminate.
[0058] (3) The nanocrystalline laminate of step (2) was crushed by a convex roller with pyramid-shaped convex points, the crushing pressure was 160 MPa, and the crushing was repeated twice to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet with a magnetic permeability of 135. After the crushing, the organic silicon protective film had no obvious cracks.
[0059] Comparative Example 1
[0060] A highly efficient magnetic crushing method for a low magnetic permeability nanocrystalline magnetic isolation sheet, compared with Example 1, a PET protective film with a thickness of 25 μm is used to replace the organic silicon protective film. The obtained nanocrystalline laminate is crushed using the same convex roller and under the same pressure, and the number of rolling times for reducing the magnetic permeability of the obtained nanocrystalline magnetic isolation sheet to below 150 is 12.
[0061] Comparative Example 2
[0062] A high-efficiency magnetic crushing method for a low-permeability nanocrystalline magnetic isolation sheet, compared with Example 1, a PET protective film with a thickness of 50 μm is used to replace the silicone protective film. The obtained nanocrystalline laminate is crushed using the same convex roller and under the same pressure, and the number of rolling times for reducing the magnetic permeability of the obtained nanocrystalline magnetic isolation sheet to below 150 is 26.
[0063] Comparative Example 3
[0064] A highly efficient magnetic crushing method for a low magnetic permeability nanocrystalline magnetic isolation sheet, compared with Example 1, a PET protective film with a thickness of 75 μm is used to replace the organic silicon protective film. The obtained nanocrystalline laminate is crushed using the same convex roller and under the same pressure, and the number of rolling times for reducing the magnetic permeability of the obtained nanocrystalline magnetic isolation sheet to below 150 is 30.
[0065] It can be seen from the above results that the present invention adopts a thinner and more flexible silicone protective film, which greatly improves the efficiency and quality of magnet crushing.
[0066] The tensile properties of the protective films of the embodiments and comparative examples (test specifications: 2*15 cm, test speed 10.000 mm / min, gauge length 200.000 mm) were tested, and the test results are shown in Table 1 below.
[0067] Table 1
[0068]
[0069] It can be seen from the results in Table 1 that the organic silicon protective film obtained by the present invention has significantly improved elasticity compared with conventional PET films, and can better transmit the crushing pressure to the nanocrystalline material layer, thereby achieving good crushing treatment of multi-layer nanocrystalline materials and significantly improving the efficiency of crushing magnets. At the same time, it can be seen from the results of each embodiment that the lower the molecular weight of the polyetheramine curing agent used, the higher the strength of the obtained organic silicon protective film, but the elasticity is significantly reduced; the higher the molecular weight of the polyetheramine curing agent used, the lower the strength of the obtained organic silicon protective film, and the significantly improved elasticity. When the polyetheramine curing agent uses an amino-terminated polyoxyethylene ether with a molecular weight of 1000 to 3000, it can achieve good strength and elasticity at the same time, thereby achieving efficient and high-quality crushing magnets.
[0070] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An efficient magnetic crushing method for low magnetic permeability nanocrystalline magnetic isolation sheets, characterized in that: The steps include: (1) The composite multilayer nanocrystalline strip is attached by double-sided adhesive and then covered with a protective film; (2) crushing the multilayer nanocrystalline strip with the protective film on the surface in step (1) by using a convex roller to obtain a low magnetic permeability nanocrystalline magnetic isolation sheet; The protective film in step (1) is an organic silicon protective film prepared by the following method: 1) mixing hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent, then adding a chloroplatinic acid isopropanol solution catalyst and heating for reaction to obtain an epoxy polysiloxane solution; 2) The epoxy polysiloxane solution obtained in step 1) is mixed evenly with the polyetheramine, and dried and cured to form a film to obtain an organosilicon protective film.
2. The high-efficiency magnetic crushing method of a low-permeability nanocrystalline magnetic isolation sheet according to claim 1 is characterized in that: The thickness of the double-sided tape in step (1) is 1 to 5 μm; the thickness of the nanocrystalline ribbon is 14 to 25 μm; the number of layers of the nanocrystalline ribbon is 2 to 4; and the thickness of the protective film is 5 to 50 μm.
3. The high-efficiency magnetic crushing method of a low-permeability nanocrystalline magnetic isolation sheet according to claim 1 is characterized in that: The hydrogen-containing silicone oil in step 1) is a hydrogen-containing silicone oil with a number average molecular weight of 1000 to 10000 and a hydrogen content of 0.2 to 1 wt.%; the amount of allyl glycidyl ether used is 5% to 30% of the mass of the hydrogen-containing silicone oil.
4. The high-efficiency magnetic crushing method of a low-permeability nanocrystalline magnetic isolation sheet according to claim 1 is characterized in that: The organic solvent in step 1) is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol; the amount of the organic solvent is 100% to 200% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether.
5. The high-efficiency magnetic crushing method of a low-permeability nanocrystalline magnetic isolation sheet according to claim 1 is characterized in that: The temperature of the heating reaction in step 1) is 80-90° C. and the time is 2-8 hours.
6. The high-efficiency magnetic crushing method of a low-permeability nanocrystalline magnetic isolation sheet according to claim 1, characterized in that: The polyetheramine in step 2) is amino-terminated polyoxypropylene ether and amino-terminated polyoxyethylene ether with a molecular weight of 400-5000; the amount of the polyetheramine is 50%-150% of the total mass of hydrogen silicone oil and allyl glycidyl ether.
7. The high-efficiency magnetic crushing method of low-permeability nanocrystalline magnetic isolation sheet according to claim 6, characterized in that: The polyetheramine is an amino-terminated polyoxyethylene ether with a molecular weight of 1000-3000.
8. The high-efficiency magnetic crushing method of low-permeability nanocrystalline magnetic isolation sheet according to claim 1, characterized in that: The drying and curing film-forming in step 2) refers to coating drying and curing film-forming or casting drying and curing film-forming at a temperature of 60 to 100°C.
9. The high-efficiency magnetic crushing method of low-permeability nanocrystalline magnetic isolation sheet according to claim 1, characterized in that: The convex point roller in step (2) is a convex point roller with pyramid-shaped convex points; the crushing pressure is 10 to 200 MPa.
10. The high-efficiency magnetic crushing method of low-permeability nanocrystalline magnetic isolation sheet according to claim 1, characterized in that: The crushing in step (2) refers to crushing to a magnetic permeability of less than 500.
Citation Information
Patent Citations
Method for preparing organic silicon modified chitosan membrane
CN105037768A
Preparation process and preparation equipment of amorphous nanocrystalline magnetic sheet
CN110993310A
Wireless charging shielding sheet and preparation method thereof, wireless charging module and magnetic crushing equipment
CN112467824A
Epoxy group-containing organosilicon compound and preparation method thereof, and epoxy resin composition and preparation method thereof
CN112574418A
Nanocrystalline magnetic sheet continuous crusher capable of testing and sorting magnetic sheets on line
CN209271531U